“Populism at home, revisionism in the world”: the case of Turkey's peacemaking engagement in a changing world order - Sofos, Spyros A. (Frontiers in Political Science, 2025)
Populism has emerged as a transformative force in global politics, questioning the legitimacy of liberal democratic institutions and reshaping the contours of foreign policy—especially in emerging powers governed by populist leadership. This article investigates the intersection between domestic populist governance and international revisionism, focusing on Turkey under President Recep Tayyip Erdogan and the Justice and Development Party (AKP). It argues that populism in power reconfigures not only the institutional architecture of the domestic political arena but is also conducive to revisionist agendas at the international level. This revisionist ambition is anti-institutional at its core, averse to processes of mediation and deliberation and favors more personalistic, less transparent politics, usually affirming the leader's direct, personalized mandate from “the people”. In Turkey's case, this transformation marks a departure from the founding Kemalist principle of “Peace at home, peace in the world” toward a more assertive foreign policy orientation that might be described as “Revisionism at home, revisionism in the world.” The AKP's discourse merges sovereignty and injustice into a populist logic that positions Turkey as both a regional power and a moral actor in global politics. This revisionist posture has been especially evident in Turkey's peacemaking engagements, where humanitarianism and diplomacy are mobilized as instruments of strategic assertion. The central question guiding this analysis is: What is the relationship between Turkey's domestic populist political imagination and its revisionist foreign and peacebuilding policies? And what does this relationship reveal about the international behavior of populist regimes more broadly? These questions are addressed through a focus on Somalia. With Turkey's strategic presence in the country spanning over 15 years, the case of Somalia offers a critical vantage point to observe Turkey's shift from reformist multilateralism to populist-revisionist assertiveness, and a critical site in which domestic narratives of injustice, contested sovereignty, and national vindication are projected outward and reconfigured as a distinctive mode of international engagement. Methodologically, the article adopts a discursive approach, treating discourse as both performative and constitutive—a practice that not only represents but enacts political realities. It emphasizes how populist-revisionist foreign policy is animated by symbolic narratives, historically situated emotional economies, and appeals to national memory and grievance. This analysis highlights how populist leaders translate domestic logics of sovereignty, justice, and moral exceptionalism into international conduct, contributing to an emerging foreign policy paradigm that disrupts liberal international norms. By examining Turkey's evolving international engagements, this article offers insight into how populism travels across scales—from domestic arenas to the global stage—reshaping not only institutions but the meanings and practices of foreign policy itself.